European Humanities in the Perception of Chinese Students: A Reflection Based on A Personal Teaching Experience - Untea, Ionut (ETHICS IN PROGRESS, 2019)
As a young teacher and researcher, the prospective of introducing western philosophical themes to a public of students from a non-western country, came in 2016 as a once-in-a lifetime opportunity, which I met with great enthusiasm. However, as in any situation involving pre-conceived expectations, facing and dealing with the real situation on the ground opens up a pathway for a closer understanding of both the new culture explored, a perception of one’s own limits and the willingness to overcome them. The following lines are intended to cover the way my approach to teaching to a Chinese public has evolved from pre-conceptions and empty enthusiasm to an attitude of pedagogical creativity in identifying and presenting the key topics that would attract my students’ attention. As I will show, students’ expectations were to approach the western ideas not directly, but via a more complex process of being acquainted with the major historical and cultural movements in Europe and the western world. This meant the involvement in the teaching process of a wider number of elements taken not only from philosophy but from other humanistic disciplines.